2013
DOI: 10.1210/jc.2012-4287
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Vitamin D2and D3in Healthy Volunteers, a Randomized Placebo-Controlled Trial

Abstract: Vitamin D3 increases the total 25(OH)D concentration more than vitamin D2. Vitamin D2 supplementation was associated with a decrease in 25(OH)D3, which can explain the different effect on total 25(OH)D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
112
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 30 publications
12
112
1
Order By: Relevance
“…Perhaps the most complete study investigating the comparative effects of these therapies in a healthy population was conducted by Lehmann et al [31], who showed that cholecalciferol was superior to ergocalciferol in increasing 25(OH)D levels. However, this study was conducted in community-dwelling adults without CKD, and so this investigation may not be generalizable to a CKD population that possesses inherent defects in pathways that regulate vitamin D metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most complete study investigating the comparative effects of these therapies in a healthy population was conducted by Lehmann et al [31], who showed that cholecalciferol was superior to ergocalciferol in increasing 25(OH)D levels. However, this study was conducted in community-dwelling adults without CKD, and so this investigation may not be generalizable to a CKD population that possesses inherent defects in pathways that regulate vitamin D metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Serum 25(OH)D 3 concentrations at baseline and after 8 and 12 weeks of intervention were quantified by means of a MassChrom ® 25-OH Vitamin D 3 reagent kit (Chromsystems GmbH, Munich, Germany) for LCeMS/MS using an API 2000™ system (Applied Biosystems, Darmstadt, Germany) as described elsewhere [15]. The lower limit of quantification (LLOQ) was 10.7 nmol/L and the coefficients of variance were 8.3% (n ¼ 4, inter assay) and 5.0% (n ¼ 3, intra assay) at 39.9 nmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…Based on clinical studies, vitamin D3 has shown to more effectively increase 25-hydroxyvitamin D 3 serum levels than vitamin D2 (12).…”
mentioning
confidence: 99%